A Systematic Review Exploring Variables Related to Bystander Intervention in Sexual Violence Contexts. (July 2023) - Mainwaring, Chelsea; Gabbert, Fiona; Scott, Adrian J.
This article presents a systematic review of the available literature which has investigated the role of key variables in facilitating or inhibiting bystander intervention (including direct intervention, tertiary and secondary prevention) in sexual violence (SV) contexts. Studies exploring the role of individual, situational and contextual variables were grouped to provide a narrative overview of bystanders' personal characteristics as well as the immediate and wider contexts which may be influencing their bystander behaviour. A systematic search of published literature from four electronic databases identified 2526 articles that were screened, of which 85 studies met the inclusion criteria. Most studies focused upon the role of individual variables, in particular gender of bystander. This body of work finds females are more likely to intervene than males; however, not all studies report these differences and in some cases, this is influenced by the type of intervention behaviour being considered. Regarding situational variables, the most commonly researched variable was the presence of other bystanders, although the role of this variable as inhibiting or facilitating was not clear. Finally, the most commonly researched contextual variable was social norms towards intervention, which has consistently shown greater bystander intervention when there is a belief that peers support such behaviour. Very few studies considered the interaction between these variables. Therefore, it is important for future research to consider this gap in the literature so that we can obtain a more well-rounded understanding of variables that can inhibit and facilitate bystander intervention in SV contexts.